Comparison of Tumor Seeding and Recurrence Rate After Laparoscopic vs. Open Nephroureterectomy for Upper Urinary Tract Transitional Cell Carcinoma - Simone Morselli; Simone Morselli; Ferdinando Daniele Vitelli; Giorgio Verrini; Arcangelo Sebastianelli; Arcangelo Sebastianelli; Riccardo Campi; Riccardo Campi; Andrea Liaci; Pietro Spatafora; Pietro Spatafora; Paolo Barzaghi; et al. (Frontiers in Surgery, 2021)
Introduction: Laparoscopic surgery for Upper Urinary Tract Urothelial Cell Carcinoma (UTUC) is still debated for its possible seeding risk and thus consequent oncological recurrences, especially for atypical ones. The aim of the study is to compare recurrence and survival after Laparoscopic vs. Open Radical Nephroureterectomy (RNU) for Upper Urinary Tract Urothelial Cancer (UTUC).Method: A retrospective evaluation of UTUC consecutive surgeries from 2008 to 2019 was conducted, including pT ≥ 2, High Grade UTUC who underwent RNU with bladder cuff excision without concomitant lymphadenectomy in three urological tertiary centers. Statistical analyses compared recurrence and cancer specific survival, based on surgical approach, while logistic multivariate analyses and Kaplan Meyer survival curve analyzed possible risk factors for recurrence and survival.Results: One hundred seven cases of RNU, 47 (43.9%) laparoscopic and 60 (56.1%) open, were included in this report. Preoperative characteristics were comparable between groups. However, tumor stage was higher in the Open arm [T3–T4 in 44 (73.3%) vs. 20 (43.4%) in Laparoscopic]. Mean follow-up was 91.6 months in laparoscopy RNU vs. 93.5 months in open RNU. Recurrence rate (RR) was comparable between groups (p = 0.594), and so was the site, although 3 (6.3%) peritoneal recurrences were found only in laparoscopic group (p = 0.057). At multivariate logistic regression, tumor stage and surgical approach were independent predictors of recurrence (p < 0.05), while only tumor stage was predictor of cancer specific death (p = 0.029).Conclusion: Surgical approach has no impact on recurrence site, overall survival, and RR. Still, according to our data peritoneal carcinomatosis was present only in laparoscopic arm, despite how it didn't reach statistical significance.